Teacher Experiences of In-Service Training Programmes on Curriculum Differentiation and Modification in Inclusive Primary Schools of Capricorn District, Limpopo Province, South Africa - Maite E. Maebana (International Journal of Membrane Science and Technology, 2023)
Many teachers struggle with curriculum differentiation and curriculum modification in an inclusive education setting, despite a range of in-service training programmes being offered over recent years. More specifically, several training initiatives have focused on the development of school managers, with the idea of them cascading the information down to the other staff members at school. In this article, we report on teacher experiences of in-service training programmes on curriculum differentiation and modification in inclusive primary schools in the Limpopo Province, South Africa. In undertaking the study, we followed a qualitative approach, adopting a case study design. Two officials from the Inclusive Education section of the Department of Education and six teachers from the Dimamo circuit were purposively selected to take part in the study. Data were generated through semi-structured interviews and document analysis. The generated data were analysed through content analysis. The findings of the study indicate that the participating teachers felt inadequately trained to implement various strategies that may accommodate learners with diverse needs in their classrooms, with school managers not providing feedback to teachers after attending inservice training sessions due to time constraints. As a result, we posit that the current model of teacher empowerment on curriculum differentiation and modification, which takes the form of in-service training programmes, is ineffective. we propose that new strategies should be put in place to better equip teachers in this field through, for example, short learning programmes on curriculum differentiation and modification, resource allocation, and feedback provision.